Association Between Early Stage-Related Factors and Mortality in Patients with Exertional Heat Stroke: A Retrospective Study of 214 Cases - Liu S; Xing L; Wang Q; Xin T; Mao H; Tao Y; Zhao J; Li X; Li C; Li Q; Dou Y; Li Y; et al. (International Journal of General Medicine, 2021)
Shuyuan Liu,1,2,* Ling Xing,1,3,* Qian Wang,4 Tianyu Xin,2 Handing Mao,1 Ye Tao,5 Jinbao Zhao,2 Xin Li,4 Cong Li,1 Qinghua Li,6 Yan Dou,7 Yixin Li,8 Wei Zhang,9 Bo Ning,10 Qing Song1 1Medical School of Chinese PLA, Beijing, People’s Republic of China; 2Emergency Department, Sixth Medical Center, Chinese PLA General Hospital, Beijing, People’s Republic of China; 3Department of Emergency, Beijing Tongren Hospital, Capital Medical University, Beijing, People’s Republic of China; 4Emergency Department, Third Medical Center, Chinese PLA General Hospital, Beijing, People’s Republic of China; 5Health Care Department, Beijing Huangsi Aesthetic Surgery Hospital, Beijing, People’s Republic of China; 6Department of Intensive Care Unit, The 990th Hospital of Chinese PLA, Zhumadian, People’s Republic of China; 7Department of Intensive Care Unit, The 909th Hospital of Chinese PLA, Zhangzhou, People’s Republic of China; 8Department of Intensive Care Unit, The 910th Hospital of Chinese PLA, Quanzhou, People’s Republic of China; 9Emergency Department, The 900th Hospital of Chinese PLA, Fuzhou, People’s Republic of China; 10Department of Intensive Care Unit, Air Force Medical Center of China, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bo NingDepartment of Intensive Care Unit, Air Force Medical Center of China, Beijing, 100142, People’s Republic of ChinaTel +86 15611161110Fax +86 1068410099Email boningbn@163.comQing SongMedical School of Chinese PLA, Beijing, 100853, People’s Republic of ChinaTel +86 13911374534Fax +86 1068182255Email songqing_sq87@163.comObjective: The purpose of this study is to evaluate the factors involved in the early stage of exertional heat stroke (EHS) that are associated with mortality.Methods: In this retrospective, case-control study, patients from 11 tertiary medical centers in China were enrolled from January 1, 2012, to December 31, 2019. Demographic information, underlying diseases, ambient temperature, and relative humidity, clinical manifestations, initial body temperature, time from onset to diagnosis of EHS (including suspected), and the duration of body temperature > 38°C of all enrolled patients were recorded. The occurrence of organ dysfunction within 72 h was evaluated, and in-hospital deaths were recorded. The patients were subsequently divided into a survival group and a non-survival group. The “case” refers to patients in the non-survival group, while the “control” refers to patients without death.Results: Of the 214 hospitalized patients with EHS, 183 survived and 31 died, and the overall mortality was 14.49% (31/214). A binary logistic regression showed that only the duration of body temperature > 38°C (OR 1.80, 95% CI 1.34– 2.42) and the number of organs damaged within 72 h of onset (OR 6.54, 95% CI 2.31– 18.56) were statistically significant in terms of risk of death in hospital (p < 0.05). A goodness of fit test produced a p-value of 0.76. According to receiver operating characteristic curve (ROC) analysis, the areas under the curve (AUC) were 0.989 (95% CI 0.978– 1.000; p < 0.05) and 0.936 (95% CI 0.896– 0.976; p < 0.05).Conclusion: Of the various factors involved in the early stage of the disease, the duration of high body temperature and the number of organs damaged within 72 h of onset were independent risk factors and predictors associated with death.Keywords: heat stroke, exertional, cooling, mortality